Mangiferin in combination with primaquine reduces disease progression and transmission potential while alleviating cerebral pathology through suppression of neural cell apoptosis in experimental cerebral malaria - Subham Halder; Saikat Mukherjee; Soubhik Ghosh; Poulomi Khamaru; Abhishek Choudhury; Pronabesh Ghosh; Altamas Hossain Daptary; Sayandeep Brahma; Atrayee Sengupta; Bidisha Chatterjee; Arindam Bhattacharyya (Inflammopharmacology, 2026)

Growth enhancement and rhizosphere colonization of Chilli (Capsicum annuum) by Enterobacter hormaechei - Bikram Dhara; Entaj Tarafder; Dong-Qin Dai; Subham Sarkar; Ayush Bagchi; Upasana Ghosh; Liana Mukherjee; Aishee Hazra; Arup Kumar Mitra (World Journal of Microbiology and Biotechnology, 2026)

Influence of Potassium Management on Physiology and Biochemical Activities of Lentil (Lens culinaris M.) Grown Under Rainfed Condition in Different Tillage and Sowing Time Scenario - Ramprosad Nandi; Subham Mukherjee; Kh. Chandrakumar Singh; Madhumonti Saha; Priyanka Ghatak; Arnab Kundu; Subhadip Saha; Prasanta Kumar Bandyopadhyay; Rajib Nath (Journal of Soil Science and Plant Nutrition, 2025)

Evaluating the bioactivity of Trichoderma asperellum against Colletotrichum siamense and its growth-promoting effects on Aloe vera (Aloe barbadensis Mill.) - Ankur Mukhopadhyay; Soumik Mukherjee; Subham Dutta; Sahely Kanthal; Goutam Mondal (European Journal of Plant Pathology, 2025)

First report of Colletotrichum siamense causing leaf spot of Aloe vera (Aloe barbadensis Mill.) in India - Ankur Mukhopadhyay; Soumik Mukherjee; Subham Dutta; Goutam Mondal (Australasian Plant Pathology, 2025)

Petrogenesis of magmatic charnockite-biotite granite suite from parts of the Chotanagpur Granite Gneissic Complex (CGGC), eastern Indian shield: Implication for the break down of the Columbia Supercontinent - Somdipta Chatterjee; Subham Mukherjee; Sanjoy Sanyal; Pulak Sengupta (Lithos, 2024)

On the factors controlling the incorporation of aluminium within titanites: a case study from medium pressure calc-silicate granulites in parts of the East Indian shield - Sirina Roy Choudhury; Anindita Dey; Subham Mukherjee; Sanjoy Sanyal; Subrata Karmakar; Pulak Sengupta (Mineralogy and Petrology, 2023)

Petrogenesis and in situ U-Pb zircon dates of a suite of granitoid in the northern part of the Central Indian tectonic Zone: Implications for prolonged arc magmatism during the formation of the Columbia supercontinent - Arimita Chakrabarty; Subham Mukherjee; Shreya Karmakar; Sanjoy Sanyal; Pulak Sengupta (Precambrian Research, 2023)

Formation of aluminous clinopyroxene-ilmenite-spinel symplectic assemblage in a regionally metamorphosed calc-silicate granulite from the Chotanagpur Granite Gneiss Complex, East Indian shield - Sirina Roy Choudhury; Anindita Dey; Subham Mukherjee; Sukanya Sengupta; Sanjoy Sanyal; Subrata Karmakar; Pulak Sengupta (Lithos, 2023)

Evaluation of catchment hydrology and soil loss in non-perennial river system: a case study of Subarnarekha Basin, India - Rituparna Acharyya; Niloy Pramanick; Subham Mukherjee; Subhajit Ghosh; Abhra Chanda; Indrajit Pal; Debasish Mitra; Anirban Mukhopadhyay (Modeling Earth Systems and Environment, 2022)

Evolution of the Parvalbumin Genes in Teleost Fishes after the Whole-Genome Duplication - Subham Mukherjee; Oldřich Bartoš; Kamila Zdeňková; Petr Hanák; Petra Horká; Zuzana Musilova (Fishes, 2021)
Parvalbumin is considered a major fish allergen. Here, we report the molecular evolution of the parvalbumin genes in bony fishes based on 19 whole genomes and 70 transcriptomes. We found unexpectedly high parvalbumin diversity in teleosts; three main gene types (pvalb-α, pvalb-β1, and pvalb-β2, including oncomodulins) originated at the onset of vertebrates. Teleosts have further multiplied the parvalbumin gene repertoire up to nine ancestral copies—two copies of pvalb-α, two copies of pvalb-β1, and five copies of pvalb-β2. This gene diversity is a result of teleost-specific whole-genome duplication. Two conserved parvalbumin genomic clusters carry pvalb-β1 and β2 copies, whereas pvalb-α genes are located separately in different linkage groups. Further, we investigated parvalbumin gene expression in 17 tissues of the common carp (Cyprinus carpio), a species with 21 parvalbumin genes in its genome. Two pvalb-α and eight pvalb-β2 copies are highly expressed in the muscle, while two alternative pvalb-α copies show expression in the brain and the testes, and pvalb-β1 is dominant in the retina and the kidney. The recent pairs of muscular pvalb-β2 genes show differential expression in this species. We provide robust genomic evidence of the complex evolution of the parvalbumin genes in fishes.

Bulk rock and zircon geochemistry of granitoids from the Chotanagpur Granite Gneissic Complex (CGGC): implications for the late Paleoproterozoic continental arc magmatism in the East Indian Shield - Subham Mukherjee; Anindita Dey; Sanjoy Sanyal; Mauricio Ibanez-Mejia; Pulak Sengupta (Contributions to Mineralogy and Petrology, 2019)

Origin of peraluminous minerals (corundum, spinel, and sapphirine) in a highly calcic anorthosite from the Sittampundi Layered Complex, Tamil Nadu, India - Shreya Karmakar; Subham Mukherjee; Sanjoy Sanyal; Pulak Sengupta (Contributions to Mineralogy and Petrology, 2017)